Cape Verde : Eight Review Under the Policy Support Instrument; Staff Report; Press Release. (IMF Staff Country Reports; Country Report ;, 2010)
Cape Verde's economic and policy performance remains strong. Growth is expected to recover gradually in the next few years. The global economic slowdown has affected the performance of the onshore banking sector. Risks to the outlook are broadly balanced. Executive Directors support the strategy of public investment in infrastructure to crowd in private sector development. The government will need to manage carefully its debt to maintain its low risk of debt distress. The ongoing efforts to strengthen the financial sector regulation and supervision are commended.